2020
DOI: 10.18632/aging.103008
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-induced senescence of hypothalamic astrocytes contributes to aging-related reproductive function declines in female mice

Abstract: Hypothalamic astrocytes are important contributors that activate gonadotropin-releasing hormone (GnRH) neurons and promote GnRH/LH (luteinizing hormone) surge. However, the potential roles and mechanisms of astrocytes during the early reproductive decline remain obscure. The current study reported that, in intact middle-aged female mice, astrocytes within the hypothalamic RP3V accumulated senescence-related markers with increasing age. It employed an ovariectomized animal model and a cell model receiving estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…This downregulation led to neuronal cell death in co-culture assays, suggesting a pivotal role of cellular senescence, particularly in astrocytes, in excitotoxicity, which may lead to neurodegeneration and pathologies such as Alzheimer's disease and related dementias (Limbad et al, 2020 ). Subsequent findings confirmed that ovarian estradiol induces senescence of hypothalamic astrocytes and that the senescent astrocytes compromise the regulation of progesterone synthesis and GnRH secretion, which may contribute to the aging-related decline in female reproductive function (Dai et al, 2020 ). HIV and methamphetamine were shown to induce astrocyte senescence in in vitro culture and several animal models (Yu et al, 2017 ).…”
Section: Senescence Of Glial Cellsmentioning
confidence: 81%
See 1 more Smart Citation
“…This downregulation led to neuronal cell death in co-culture assays, suggesting a pivotal role of cellular senescence, particularly in astrocytes, in excitotoxicity, which may lead to neurodegeneration and pathologies such as Alzheimer's disease and related dementias (Limbad et al, 2020 ). Subsequent findings confirmed that ovarian estradiol induces senescence of hypothalamic astrocytes and that the senescent astrocytes compromise the regulation of progesterone synthesis and GnRH secretion, which may contribute to the aging-related decline in female reproductive function (Dai et al, 2020 ). HIV and methamphetamine were shown to induce astrocyte senescence in in vitro culture and several animal models (Yu et al, 2017 ).…”
Section: Senescence Of Glial Cellsmentioning
confidence: 81%
“…Importantly, there is a significant overlap between factors secreted by reactive astrocytes and SASP factors; thus, one can speculate, that activated astrocytes may, at least in part, represent a pool of senescent cells (Cohen and Torres, 2019 ). An increased level of SASP factor mRNA (TNF-α, IL-1β, IL-6, and IL-8) was detected in the hypothalamus of aged mice and in astrocytes induced to senesce by estradiol treatment in vitro (Dai et al, 2020 ). The key transcription factors mediating pro-inflammatory signals in SASP are C/EBP and NF-κB.…”
Section: Selected Aspects Of Cellular Senescence and Their Role In Brmentioning
confidence: 99%
“…However, the measurement of telomere shortening in astrocytes in vitro contradicts this idea ( Flanary and Streit, 2004 ; Szebeni et al, 2014 ). In female mice, the proportion of hypothalamic senescent astrocytes increased with age and appeared to be mainly modulated by the ovarian estradiol, which would associate astrocyte senescence with an early reproductive decline ( Dai et al, 2020 ). Bussian and colleagues measured an increase of the expression of SA-βGal in cells identified as microglia and astrocytes by transmission electron microscopy in MAPTP301SPS19 mice ( Bussian et al, 2018 ).…”
Section: The Impact Of Ageing On the Responses And Phenotypes Of Astr...mentioning
confidence: 99%
“…In a recent study, oestrogen metabolites were shown to mediate senescence of hypothalamic astrocytes in culture, exhibiting an increase in DNA damage and senescence-associated markers. 153 Although this study did not focus on other brain regions, investigating the effects of BRCA1 and oestrogen on stress-induced senescence in other cognition-associated brain regions would be of interest in the context of neurodegeneration.…”
Section: Brca1: Its Role In Sex-specific Differences Associated With Neurodegenerationmentioning
confidence: 99%